Análise filogenética de papilomavírus de bovinos e caninos no Rio Grande do Sul - Merchioratto, Ingryd (2023)
Papillomaviruses (PVs) produce proliferative lesions in cutaneous and mucosal epithelium, which may be benign or eventually evolve to malignancy. A number of PV types have been described, which may infect a variety of hosts. Although PVs are generally speciesspecific, some bovine papillomaviruses (BPVs) have been described in other species, such as horses, sheep, goats, buffalo, yaks and domestic cats. It has also been reported that PVs may be found in single or mixed infections. PV types are usually identified by phylogenetic analysis of the L1 gene. Herein, the first study of this Thesis describes a phylogenetic analysis of BPVs circulating in Rio Grande do Sul (RS) state between 2016 and 2020. In this study, DNAs from 43 samples of bovine papillomas were amplified using two degenerate primer sets, FAP59/64 and MY09/11, which are targeted at amplification of part of L1. These amplicons were phylogenetically analyzed and evaluated for amino acid sequences. An in silico analysis was also performed with 114 complete L1 sequences (GenBank) to evaluate the agreement between the phylogenetic classification of L1 versus that based on the amplified region with primers FAP59/64 and MY09/11. We identified 31 BPV-1 (72.1%), 27 BPV-2 (62.8%) and 4 BPV-6 (9.3%). Mixed BPV-1 and 2 infections were observed in 61.3% of the samples (19/31). All BPV-6 was found in simple infections. An in silico approach demonstrated that the analysis of the FAP59/64 and MY09/11 amplicons may reproduce the complete L1 classification. Furthermore, unique or rare amino acids were found in at least one L1 sequence of each type of BPV identified in the study, some of which are in potential epitopes of PVs, suggesting an immune-mediated evolution of the viruses analyzed here. The second study reports a phylogenetic analysis of PVs circulating in dogs from RS between 2017 and 2022. For this, DNA from 26 canine papilloma samples were amplified with primers FAP59/64 and/or MY09/11. An in silico analysis was also performed with 46 complete L1 sequences (GenBank) to evaluate the concordance between the classifications based on the amplifiable region by FAP59/64 and MY09/11 vs that given by the analysis of the complete CPV L1. All PVs amplified by FAP59/64 (n = 22) were classified as CPV-1. Interestingly, the PVs amplified by MY09/11 (n = 4) were classified as BPV-1, with three detected in mixed infection with CPV- 1. In conclusion, the studies in this Thesis contribute to the knowledge about PVs by: i) describing and identifying single and mixed infections by BPV and CPV in RS; ii) demonstrating the adequacy of classification of BPV and CPV based on sequences amplified by primers FAP59/64 and MY09/11; iii) raising the hypothesis that BPVs circulating in RS may be under selective pressure by the host immune response; and iv) highlighting the possibility of infection of dogs by BPV-1.